Pengembangan Media Pembelajaran Interaktif Berbasis Game Sub Materi Anatomi Fisiologi Pada Kelas X SMK Labschool UNESA 1 Surabaya - Anggraini, Iin Hayyu Findy; Novia Restu Windayani; Octaverina Kecvara Pritasari; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2026)
Game-based learning media is considered to increase student interest in learning because it combines elements of entertainment and education in one teaching tool. This study aims to create interactive learning media based on games that can help students understand the subtopic of skin anatomy and physiology in a fun and interactive way. The method applied is the ADDIE development model. The results of the assessment by material experts and media experts indicate that the designed interactive game-based learning media is included in the